Geomagnetic INGV dataset (GEOMAG), dati degli osservatori geomagnetici italiani ... : GEOMAG - Italian geomagnetic observatory dataset ... - Di Mauro, Domenico; Bagiacchi, Paolo (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2017)
This collection includes the geomagnetic data generated since 2017 at Italian geomagnetic observatories and Antarctic observatories and stations. Data are previsional in an open format. ...